Detecting Interest Cache Poisoning in Sensor Networks using an Artificial Immune Algorithm - Kim, P; Hailes, S (2008)
The objective of this paper is to investigate how a Danger Theory based Artificial Immune System - in particular the Dendritic Cell Algorithm (DCA) can detect an attack on a sensor network. The method is validated using two separate implementations: a simulation using J-sim and an implementation for the T-mote Sky sensor using TinyOS. This paper also introduces a new sensor network attack called an Interest Cache Poisoning Attack and investigates how the DCA can be applied to detect this attack in a series of experiments.